Transforming literacy teaching : a teacher's experience of implementing critical literacy and philosophy for children in a grade three South African classroom. - Anastassopoulos, Nicolette (My University, 2015)
Philosophy for Children (P4C) and Critical Literacy (CL) are orientations that embrace a socio-cultural perspective to literacy by including the life-worlds of children. They also encourage meta-cognitive thinking by encouraging children to explore written texts. The focus of this qualitative project research was to explore the impact of implementing CL and P4C in a Grade Three classroom using a Community of Enquiry, and the stimulus of a picturebook, The Tunnel by Anthony Browne, (1989). The researcher explored the impact of this intervention on the teacher as well as the children. The data collection consisted of the teacher’s reflective journal, transcripts from six Communities of Enquiry and the children’s creative writing and artwork in the form of picturebooks. The data collection indicated two main findings. Firstly, teaching in the CoE required a different discourse for the teacher. Secondly, the children’s experience of literacy was enriched by adopting a socio-cultural perspective that enabled them to explore and critique their worlds. The overall positive results indicate that implementing these two approaches enriched the children’s creative, critical and collaborative thinking, while improving relationships in the classroom. Further research could help to broaden and develop the scope of this study as it was a small-scale study in a private, middle class school in Johannesburg.